PERANCANGAN ALAT POMPA AIR DENGAN SISTEM RENDAM PENGGERAKNYA MENGGUNAKAN MOTOR LISTRIK - Rahmad syah (Jurnal Teknik Mesin dan Pembelajaran, 2020)
Abstract: The pump is a liquid suction device where its function is to drain a liquid from an area of small pressure to an area of large pressure. Submersible pump (submersible pump) is a type of pump where the work system is placed in full water, the pump is damaged if the water is not in full condition. This type of pump must have a drinking water level so that the pump can operate properly, and the life of the pump can last a long time. The submersible pump is one type of centrifugal pump. The centrifugal pump has a way of operating, the change from the fluid velocity then changes to moving as dynamically as possible through the vanes experiencing rotation in the pump housing. Keyword: Pump, Water, Centrifugal, Immerse